Novel RNA-methylase HNRNPC promotes gastric cancer tumorigenesis by triggering the lactate-induced ferroptosis resistance - Yang, Guoqiang; Shen, Lei; Cui, Mengqian; Yang, Jian (Frontiers in Immunology, 2025)
BackgroundEmerging evidence gradually indicates that lactate and iron-induced cell death plays important role in gastric cancer (GC) progression. Here, this study focused on the effect of ferroptosis-related N6-methyladenosine (m6A) modification on GC progression.MethodsThe ferroptosis-related characteristic and lactate were tested by the kits. The in vivo mice animal assay was performed by subcutaneous xenotransplantation. The glycolysis-related analysis was performed by extracellular acidification rate (ECAR) and oxygen consumption rate (OCR) analysis.ResultsThe elevated Heterogeneous Nuclear Ribonucleoprotein C (HNRNPC) expression positively fortified the aerobic glycolysis and lactate accumulation in GC. The exogenous lactate accelerated the proliferation, oxaliplatin resistance and aerobic glycolysis in GC that inhibited by HNRNPC silencing. Moreover, HNRNPC silencing up-regulated the iron concentration accumulation and ferroptosis, and the exogenous lactate and ferrostatin-1 (Fer-1, ferroptosis specific inhibitor) co-administration reduced the iron concentration. Mechanistically, MCT1 was identified as the downstream target of HNRNPC, and HNRNPC targeted MCT1 to fortify the lactate accumulation, thereby accelerating the ferroptosis resistance in GC.ConclusionsOverall, these findings revealed the novel role of ferroptosis-related HNRNPC on GC lactate accumulation and lactate-induced tumorigenesis in GC tumor microenvironment. The data revealed the importance of HNRNPC for lactate metabolism in GC tumor microenvironment, as well as the synergistic effect of HNRNPC on lactate-induced ferroptosis resistance.